2022
DOI: 10.3390/foods11101416
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effects of Two Polysaccharide Fractions from Sargassum fusiform against Diabetes Mellitus Accompanied by Dyslipidemia in Rats and Their Underlying Mechanisms

Abstract: The current study aimed to assess the anti-diabetic effects and potential mechanisms of two Sargassum fusiform polysaccharide fractions (SFPs, named SFP-1 and SFP-2). The carbohydrate-loading experiment revealed that SFP-2 could control postprandial hyperglycemia by inhibiting the activity of digestive enzymes in rats. The analysis of diabetic symptoms and serum profiles indicated that SFPs could mitigate diabetes accompanied by dyslipidemia, and SFP-2 showed better regulatory effects on body weight, food inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Many studies found that long-term drug therapies for patients with T2D would result in various side effects and generate drug resistance, while natural plant extracts have been demonstrated as alternative therapeutic agents or supplements to treat T2D by alleviating oxidative damage and hyperglycemia (34,35). Currently, the exploration of novel antidiabetic drugs or dietary supplements from natural products is a hotspot in the research field of T2D.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies found that long-term drug therapies for patients with T2D would result in various side effects and generate drug resistance, while natural plant extracts have been demonstrated as alternative therapeutic agents or supplements to treat T2D by alleviating oxidative damage and hyperglycemia (34,35). Currently, the exploration of novel antidiabetic drugs or dietary supplements from natural products is a hotspot in the research field of T2D.…”
Section: Discussionmentioning
confidence: 99%
“…Akt signaling was a crucial modulator in the cell growth, and the phosphorylation of the Akt could lead to cell proliferation [ 30 , 31 ]. GSK-3 β was confirmed to be involved in glycogen synthesis, which could decrease blood glucose [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al showed that both the polysaccharide fractions SPP-1 and PSP-1 from S. pallidum exhibited significant hypoglycemic activity in vitro and could effectively inhibit α-amylase and α-glucosidase activities [ 44 , 47 ]; similar results were proved in other studies [ 45 , 46 ]. SFP-2, SFF and SFP-7-40 obtained from S. fusiform effectively alleviate DM through different mechanisms in vivo [ 51 , 52 , 57 , 59 , 62 ]. The fractions, LMWF, UP4 and UPP, extracted from U. pinnatifida have significant hypoglycemic effects in vivo [ 38 , 56 , 60 ].…”
Section: Marine Polysaccharides With Hypoglycemic Activitymentioning
confidence: 99%
“…It was further verified that Lactobacillus , Weissella , Romboutsia , Dubosiella and Turicibacter dominate the microenvironment of the intestinal microbiota administered via ULP and contribute to ameliorate the harmful effects of diabetes on the organism [ 64 ]. SFP-2 extracted from S. fusiform can promote the growth of Muribaculaceae_norank , Akkermansia , Bifidobacterium and Lactobacillus in the guts of diabetic rats and increase the abundance of intestinal microflora [ 51 ]. Other researchers have found similar results with FU extracted from different Sargassum species because the higher ratio of fucose and galactose in them favors colon microbiota fermentation, changes the abundance of probiotics and reduces the pathogenic bacteria and promotes the intestinal microflora of diabetic rats at the normal level [ 52 , 59 ].…”
Section: Hypoglycemic Mechanisms Of Marine Fucosyl-polysaccharidesmentioning
confidence: 99%